Kemampuan Pemecahan Masalah Matematis Siswa Dengan Menggunakan Model Pembelajaran E-Learning Berbantuan Aplikasi Kaizala - Mila Parlina; Ari Septian; Sarah Inayah (LPPM Universitas Advent Indonesia, 2021)
The study is about the ability to solve a student’s mathematical problem solving before using the software kaizala in math study during the covid-19 pandemic in an effort to enhance the student’s mathematical problem capability. The subject of this research is class XI BDP 2 SMK Negeri 1 Cipanas. The method used on this research is pre-eksperimental design with research design one group pretest-posttest. The instrument used was a test of mathematical problem solving. From this research comes the result of the mathematical problem solving of final students after learning using a Kaizala application is better then the ability to solve the first student’s mathematical problem and obtained the average value of student’s mathematical problem solving ability after using kaizala application is 71,75% which means the student’s mathematical problem solving ability has good criteria.